Intercultural exposure, intercultural empathy, creative cognitive processes, and creative behaviour in South African employees - Naidoo, Juniper Jade (My University, 2021)
The current research investigated whether intercultural exposure, intercultural empathy, and creative cognitive processes are related to creative behaviour — a factor that is integral to organisational growth, ingenuity, competitiveness, and success (Ghosh, 2014; Rios et al., 2020; Waight, 2005). Literature suggests that intercultural exposure bears little significance if intercultural empathy is not taken into consideration (Hwang & Han, 2018). This research therefore also aimed to establish whether intercultural empathy moderates the relationship between intercultural exposure and creative behaviour. Furthermore, creative cognitive processes were identified as an antecedent to creative behaviour (Dunne, 2017; Lu et al., 2017; Lubart, 2001; Miller & Dumford, 2014), and therefore, this research aimed to further this understanding and establish whether creative cognitive processes use moderates the relationship between intercultural exposure and creativity. The study employed a quantitative, non-experimental, cross-sectional, and correlational design in order to determine the aforementioned relationships and predictions. 129 South African employees responded to a self-report questionnaire, through non-probability, convenience and snowball sampling. A self-developed demographic questionnaire attempted to capture the complex nature of intercultural exposure in terms of its breadth and depth. Additionally, the final questionnaire included an adapted questionnaire to assess intercultural empathy, the Creativity Scale (Tsai et al., 2015a) to assess creative behaviour in the workplace, and the Cognitive Processes Associated with Creativity Scale (CPAC) to assess creative cognitive processes use (Miller, 2014b). Descriptive statistics, Spearman’s Rho, simple regression, hierarchical multiple regression, and two-way ANOVA’s were used to evaluate the data. The results indicated various significant relationships between the variables, and intercultural empathy and one social component of intercultural exposure significantly predicted creative behaviour. There were five significant hierarchical multiple regressions which showed that creative cognitive processes use significantly altered the relationship between certain intercultural exposure variables and creative behaviour, such that those with higher levels of intercultural exposure and higher levels of creative cognitive processes use had significantly higher levels of creative behaviour compared to those individuals with lower levels of creative cognitive processes use. There were two significant two-way ANOVA’s which demonstrated that intercultural empathy facilitated creative behaviour when there were high levels of intercultural exposure and high levels of empathy, but inhibited creative behaviour when levels of intercultural empathy were low and intercultural exposure was high. Thus, intercultural empathy was shown to be a crucial component in the relationship between intercultural exposure and creative behaviour. The findings also demonstrated the importance of social intercultural contact in altering the relationships between creative cognitive processes use and intercultural empathy with creative behaviour. While there were strengths to this research, such as the importance of intercultural exposure in South Africa and the lack of existing research, as well as crucial findings regarding the role intercultural empathy plays in altering the relationship between intercultural exposure and creativity, there were also some limitations. The non experimental design prohibited causal conclusions, the sample size could have been larger, and the measurement of intercultural contact may not have been precise enough to yield consistent and thorough information regarding intercultural exposure. Despite this, the findings from the study provide valuable additional insight into the relationships between creative behaviour in the workplace and intercultural exposure, intercultural empathy, and creative cognitive processes.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Arts in the field of Organisational Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021